2008
DOI: 10.1136/gut.2008.149468
|View full text |Cite
|
Sign up to set email alerts
|

Human Sgo1 downregulation leads to chromosomal instability in colorectal cancer

Abstract: These findings suggest that hSgo1-downregulated colorectal cancers have a clinicopathological character of CIN, and hSgo1 downregulation leads to CIN in colorectal cancer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
86
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(87 citation statements)
references
References 35 publications
0
86
0
1
Order By: Relevance
“…Depletion of shugoshin results in premature separation of sister chromatids and aneuploidy in human colon cancer cells (Iwaizumi et al, 2009). It could be conjectured that removal or lack of centromere cohesin causes aneuploidy.…”
Section: Discussionmentioning
confidence: 99%
“…Depletion of shugoshin results in premature separation of sister chromatids and aneuploidy in human colon cancer cells (Iwaizumi et al, 2009). It could be conjectured that removal or lack of centromere cohesin causes aneuploidy.…”
Section: Discussionmentioning
confidence: 99%
“…Sgo1 −/+ model has shown unique transcriptomic signatures at the tissue/organ level and cancer proneness in certain organs including colon, lung, and liver (Rao et al., 2016; Yamada et al., 2012, 2015, 2016). In humans, the homolog SgoL1 is frequently mutated or abnormally expressed in cancers, affecting the mitotic process (Iwaizumi et al., 2009; Kahyo et al., 2011; Matsuura et al., 2013; Wang et al., 2015). Congenital mutations in human SgoL1 lead to chronic atrial and intestinal dysrhythmia syndrome, affecting the heart and gut rhythm (Chetaille et al., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Shugoshin-like (SGOL1) protein, the mammalian homolog of shugoshin, interacts with protein phosphatase 2A (PP2A), localizes in the centromeric region and prevents cohesin complex from precocious cleavage at the centromere through dephosphorylation of SA2, one of the cohesin subunits (Kitajima et al, 2006;Riedel et al, 2006). In a study on human cancer, we found that SGOL1 expression was decreased in colorectal cancer and that SGOL1-knockdown led to CIN in a colon cancer cell line (Iwaizumi et al, 2009). Furthermore, a crucial link between histone H2A phosphorylation and CIN through shugoshin has recently been discovered (Kawashima et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…RT-PCR was carried out as described in our previous report (Iwaizumi et al, 2009). The primer sequences used for the first RT-PCR ( Figure 1b) were 5 0 -GGAGGAGGAAGATAG CTGTTGC-3 0 (sense) and 5 0 -TATGGCAATGGCTCACTC TG-3 0 (antisense).…”
Section: Rt-pcr and Plasmid Constructionmentioning
confidence: 99%
See 1 more Smart Citation